"Hard Sciences" e "Social Sciences": Um Enfoque Organizacional - Beato F. Claudio C. (Dados: Revista de Ciências Sociais, 1998)
The article offers an empirically guided discussion of the organizational model which Whitley has proposed for analyzing scientific fields. The central, empirically tested dimensions of the model refer to a consensus-forming process. It is proposed that the model be expanded to include other dimensions related to consensus-formation in different fields: that is, the use of technologies and the division of labor.